Analisis Kebutuhan Modul Pembelajaran Fisika Berbasis Contextual Teaching and Learning untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas XI SMA Negeri Karya Sakti - Naja Seindah Hafidho; Wahyu Arini (Departement of Mathematics Education, 2024)
The needs analysis was carried out with the aim of finding out the learning needs and problems experienced by students and as a guide for solving the problems faced, then the needs analysis research was carried out. This needs analysis was carried out using qualitative methods. This analysis was carried out by conducting interviews with students and teachers. The instruments used in this research were student response questionnaires and interviews. The results of the needs analysis carried out show that the learning process carried out has not used learning modules to maximize students' critical thinking abilities. The ongoing learning process is still dominated by teachers (teacher-oriented learning), so that students who are expected to be active and interactive have not been achieved. In the Contextual Teaching and Learning (CTL) approach, the components used can help students improve their critical thinking skills. In implementing the Contextual Teaching and Learning (CTL) model, it will be more optimal if you use learning modules as open materials.